Impact of Cashew Nut Trade Policy on Household and Government Revenues in Senegal: A Dynamic Computable General Equilibrium Model Analysis - Diallo, Mamadou Abdoulaye; Coly, Samuel Maxime (European Scientific Journal, ESJ, 2022)
The objective of this paper is to assess the medium and long term sectoral impacts of a trade policy on the cashew nut sector in Senegal. Thus we used the dynamic computable general equilibrium model which was inspired by the dynamic PEP model (PEP-1-t) developed by Decaluwé et al (2010) to simulate the impact of a 10% tax on raw cashew nut exports on the sectors of activity and on household and government income. The accounting framework of the model is the 2017 Senegal Social Accounting Matrix (SAM), from which we disaggregated the agricultural branch to isolate the cashew sector. The results of the simulation showed that a policy of taxing raw cashew nut exports from Senegal at a rate of 10% would have a negative impact in the medium and long term on the value added of the cashew nut sector, as it would decrease over the period 2017 to 2022. This decline would be explained by a drop in export demand for the product, which is linked to the sector’s loss of competitiveness. On the other hand, this policy would benefit the other sectors, particularly the agricultural sector for which the value added would increase during the period. This policy would also negatively affect the income and savings of urban and rural households. However, the government would benefit from the measure since its income would increase over the period.